1885 N.C. Sess. Laws 382 - (:unkn) unknown (My University, 1885)
Pub. Laws, ch. 207, §§ 1-2: That nothing in section two thousand eight hundred and thirty-four of The Code shall be so construed as to prevent the farmers in Pamlico county from shooting larks, doves and partridges on their own premises, when the same are doing injury to their crops.
Keywords: HUNTING REGULATION